2019
DOI: 10.3762/bjnano.10.5
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of tarsal morphology and traction force in the two burying beetles Nicrophorus nepalensis and Nicrophorus vespilloides (Coleoptera, Silphidae)

Abstract: Our aim was to compare friction and traction forces between two burying beetle species of the genus Nicrophorus exhibiting different attachment abilities during climbing. Specifically, the interaction of adhesive hairs and claws during attachment with respect to various surface properties was investigated by using a 2 × 3 experimental design. Traction force was measured for two different surface energies (hydrophilic vs hydrophobic) varying in roughness from smooth to micro-rough to rough. Nanotribometric test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…For Seta-II (figure 1 b ), the seta was developed as a square column with a uniform cross-section to facilitate manufacture. The design of the spatula was influenced by the spatula-like structure of insects, where the seta is smoothly attached to the spatula [31]. Furthermore, the transitional characteristics of the joints resulted in an augmentation of the spatula’s thickness, which was arranged from 100 nm at the proximal end to 10 nm at the distal end.…”
Section: Design and Finite Element Model Of Seta Geometric Prototypesmentioning
confidence: 99%
“…For Seta-II (figure 1 b ), the seta was developed as a square column with a uniform cross-section to facilitate manufacture. The design of the spatula was influenced by the spatula-like structure of insects, where the seta is smoothly attached to the spatula [31]. Furthermore, the transitional characteristics of the joints resulted in an augmentation of the spatula’s thickness, which was arranged from 100 nm at the proximal end to 10 nm at the distal end.…”
Section: Design and Finite Element Model Of Seta Geometric Prototypesmentioning
confidence: 99%
“…Considering that attachment organs for locomotion are one of the most essential interfaces between organisms and their environment, the evolution of these organs was crucial for many arthropods that prowl or crawl on various substrata. The tip shape of these fibrillar structures is diverse among species and even within a single attachment pad [4,[6][7][8], resulting in a wide variety of terrestrial and aquatic surfaces that animals can walk on and adhere to.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to this effect, the grease layer on the female body surface could reduce tarsal adhesion [12,24,25]. Moreover, stiffness, chemistry, texture and humidity of substrates are also known to influence attachment forces [7,9,[26][27][28][29][30][31][32][33][34][35][36][37]. Until now, these effects have been well studied on artificial flat smooth and rough surfaces, but rarely in the context of copulation that never occurs on flat surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Many insects have claws and/or hairy or smooth attachment pads, which they use to walk stably [1][2][3][4][5]. In particular, the ability to attach to surfaces using attachment pads has been investigated in many insects, including stick insects [3,[6][7][8][9][10], beetles [4,[11][12][13][14][15], cockroaches [16][17][18][19], and flies [20,21]. These investigations have found that similar to geckos', insects' attachment pads generate significant van der Waals forces [22][23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%